Membangun Character Building bagi Anak Difabel dalam Pembelajaran Pendidikan Agama Islam - Isti, Istiqomah Faiz; Widodo, Hendro (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2019)
This article aims to examine the realm of planting and character development for children with disabilities in learning Islamic religious education at SD NU Sleman. This study is a field research with a descriptive qualitative approach. Data analysis techniques were carried out using the Spradley model, namely data analysis carried out in conjunction with data collection consisting of domain analysis, taxonomic analysis, compound analysis, and data analysis. The results of this study indicate that character planting must be built for children with disabilities in NU Elementary School, namely about independence, self-acceptance and social, and self-confidence, especially in school. By planting this character, disabled participants did not get negative perceptions by other normal students. Instead normal students appreciate and admire the persistence of learning disabled students. NU Elementary School has an integrated curriculum in PAI learning so that the formation of the akhlaqul karimah character is increasingly realized. Students with disabilities or those with other special needs have the right to receive the same Islamic education despite the limitations. In determining the material, objectives, and methods of learning Islam, religious teachers consider the ability, depth of material, methods, and time available.